UPAYA MENINGKATKAN HASIL BELAJAR MATA PELAJARAN PKn DENGAN MENGGUNAKAN MODEL PEMBELAJARAN QUIS TEAM DI KELAS XI IPS3 SEKOLAH MENENGAH ATAS NEGERI 8 PONTIANAK - TITIK SUKMAWATI (JARDIKNAS - Jurnal Pendidikan dan Sosial, 2021)
This research was conducted to determine how to improve student outcomes in the Quis team model of learning outcomes in Pancasila and citizenship education subjects in class XI IPS 3, semester 1, 2018/2019 academic year at SMA Negeri 8 Pontianak. The purpose of this study is to improve student outcomes in Citizenship Education learning. The type of research used was Classroom Action Research (PTK) which consisted of two cycles and each cycle consisted of two meetings. The research subjects were 36 students of class XI IPS 3. Based on the results of the research, it was found that there was an increase in the learning outcomes of civic Pancasila Education using the Quis team model for class XI IPS 3 students at Public Senior High School 8 Pontianak. This is proven by an increase in the learning outcomes of Pancasila Civics Education which is quite good, namely in the first cycle with an average value of 73.89, so the increase is 13.81%. while the average value in cycle II was 86.88, so the increase was 33.6%.